Coronary flow reserve is impaired in patients with nonalcoholic fatty liver disease: Association with liver fibrosis - ÇELİKEL, ÇİĞDEM; YILMAZ, YUSUF (ELSEVIER IRELAND LTD, 2010)
Background: Nonalcoholic fatty liver disease (NAFLD) is associated with an increased risk of cardiovascular disease. Coronary flow reserve (CFR) is widely used to examine the integrity of coronary microvascular circulation. We evaluated the prevalence of impaired CFR in patients with biopsy-proven NAFLD. We also investigated the independent clinical, biochemical, and liver histology predictors of CFR in the setting of NAFLD. Methods: Fifty-nine consecutive patients with NAFLD and 77 age- and gender-matched controls were evaluated. CFR recordings were performed by transthoracic Doppler harmonic echocardiography. CFR >= 2.0 was considered normal. Results: CFR was significantly lower in patients with NAFLD than in controls (2.11 +/- 0.45 vs. 2.52 +/- 0.62, P < 0.001). An impaired CFR (i.e. < 2) was found in 25 NAFLD patients (42.4%) whereas all controls had normal CFR values (P < 0.001). A stepwise linear regression analysis in NAFLD patients identified liver fibrosis scores as the only independent predictor of CFR values (beta = -0.60; t = -2.44, P = 0.021). Conclusion: Our findings indicate that in patients with biopsy-proven NAFLD: (a) an abnormal CFR is found in approximately 42.4% of cases, and (b) liver fibrosis scores are an independent predictor of depressed CFR. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: Transthoracic Doppler harmonic echocardiography; Coronary flow reserve; Nonalcoholic fatty liver disease; Liver biopsy; SERUM ADIPONECTIN LEVELS; INTIMA-MEDIA THICKNESS; ENDOTHELIAL DYSFUNCTION; HYPERTENSIVE PATIENTS; METABOLIC SYNDROME; ABNORMALITIES